Meta-análise de bancos de microarray para avaliação da expressão de indoleamina 2,3-dioxigenase e de genes relacionados à via do receptor de hidrocarboneto de arila em câncer de bexiga - Cecconi, Guilherme Falato (2018)
Bladder cancer (BC) is one of the most common neoplasms in man, accounting for high morbidity and mortality, even having classic therapeutic protocols. Immunotherapy is emerging as a promising strategy for the treatment of BC. Among the candidate molecules is indoleamine 2,3-dioxygenase (IDO), an enzyme recognized as immunomodulatory since it has been described in placenta protecting the embryo against the maternal immune system. IDO chemical inhibitors have been proposed in the area of oncology so that the immune escape of tumors is overcome. Since INF-ɤ is its main inductor, IDO acts by the activation of the aryl hydrocarbon receptor (AHR). However, there is little IDO study in bladder cancer and studies investigating the expression of IDO in general tumors show that the enzyme is present in most neoplasms, but there is high variability among individuals. The aim of the present study was to analyze the expression of IDO, INF-ɤ, AHR and CYP1A1 (marker of AHR activation) in normal and non-muscle invasive bladder tumor (CBNMI) and invasive muscle (CBMI) , in order to verify the possibility of IDO being targeted as a therapeutic target in this type of neoplasia. The method was based on the analysis of databases (series) of microarray published in NCBI (National Center of Biotechnology Information) and made via GEO Datasets (Gene Expression Omnibus). For this, the descriptor "Bladder cancer" was used. At first, we selected series that offered analysis of normal human tissues for the validation of the correlation between the genes analyzed. Next, we selected series that offered analysis of normal bladder versus bladder cancer or between CBNMI versus CBMI. Of 3,110 series selected with the descriptor "bladder cancer", 123 were microarray studies and 12 offered the analyzes of interest. The statistical analysis was performed by the GEO2R application offered by the GEO Datasets platform, which uses the statistical method. Correlation and survival analyzes (only one series) were performed by the SPSS program version 22. As results, there is a positive correlation between the genes analyzed for normal tissues such as placenta, lymph node and intestine. Of the eight series that offered comparison between normal bladder and bladder cancer, none showed differences in the expression of IDO, INF-ɤ and CYP1A1. In only one series was there an increase in AHR in bladder cancer. The same profile was found by comparing normal bladder tissue versus CBNMI or CBMI. In the comparison between CBNMI and CBMI, there was an increase in the expression of IDO in two of the 8 series, and CYP1A1 was also increased in one of them. In correlation analysis, in only approximately 50% of the series the IDO correlated with INF-ɤ, AHR and CYP1A1. There was a negative correlation between IDO expression and patient survival in one of the series, but the Kaplan Meier analysis showed no difference between the group with low IDO expression and the high expression group. The results demonstrate that IDO expression may be increased in BC, but there is great variability among individuals. In BC, the relationship between the genes studied does not hold steady as it does in normal tissues. The study points to the importance of characterizing the IDO-AHR pathway in patients with BC in order to institute personalized immunotherapy.